Successful Treatment of Staphylococcus aureus Prosthetic Joint Infection with Bacteriophage Therapy - Claudia Ramirez-Sanchez; Francis Gonzales; Maureen Buckley; Biswajit Biswas; Matthew Henry; Michael V. Deschenes; Bri’Anna Horne; Joseph Fackler; Michael J. Brownstein; Robert T. Schooley; Saima Aslam (Viruses, 2021)
Successful joint replacement is a life-enhancing procedure with significant growth in the past decade. Prosthetic joint infection occurs rarely; it is a biofilm-based infection that is poorly responsive to antibiotic alone. Recent interest in bacteriophage therapy has made it possible to treat some biofilm-based infections, as well as those caused by multidrug-resistant pathogens, successfully when conventional antibiotic therapy has failed. Here, we describe the case of a 61-year-old woman who was successfully treated after a second cycle of bacteriophage therapy administered at the time of a two-stage exchange procedure for a persistent methicillin-sensitive Staphylococcus aureus (MSSA) prosthetic knee-joint infection. We highlight the safety and efficacy of both intravenous and intra-articular infusions of bacteriophage therapy, a successful outcome with a single lytic phage, and the development of serum neutralization with prolonged treatment.